Female genital mutilation among children in Ethiopia: A time-to-event analysis of age at circumcision. - Michael Arthur Ofori; Daniel Biftu Bekalo; David Kwamena Mensah; Niharika Jha (PLoS ONE)
Female Genital Mutilation (FGM) has become a global health concern. It is a deeply entrenched harmful practice involving partial or total removal of the external female genitalia for non-medical reasons. To inform effective policymaking and raise awareness about FGM's health risks, understanding socioeconomic and demographic factors influencing the timing of girls' circumcision is crucial. This study employed semi-parametric survival models to examine the association between residential status and time-to-circumcision of girls in Ethiopia. The data used in this study was the 2016 Ethiopian Demographic and Health Survey (EDHS) report, which was conducted by the Central Statistical Agency (CSA). The analysis revealed that residential status (rural vs urban, HR = 1.73: 1.35-2.70), religion (Muslim vs Christian, HR = 1.51: 1.38-2.70), mother's educational level (none vs higher, HR = 5.25: 2.23-12.36 or primary vs higher HR = 4.12: 1.25-9.68), father's educational level (none vs higher, HR = 1.65: 1.12-2.43), and mother's age (15-24 years vs 35 +, HR = 1.89: 1.21-2.95 or 24-34 years vs 35 +, HR = 1.55: 1.18-2.02) are significant risk factors for age at circumcision. Mother's age and family wealth index were time dependent risk factors. Effective interventions to reduce FGM prevalence would need to address multiple aspects simultaneously, including improving access to education (especially for girls and women), targeting both urban and rural areas with awareness campaigns, and considering culturally sensitive approaches that take into account religious and traditional beliefs while promoting the health and rights of girls and women.